Effect of Promotion and Price on Customers' Purchase Interests at PT Sumber Cipta Multiniaga, South Jakarta Branch - Juhaeri Juhaeri (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
This study aims to determine the effect of promotion and price on customer buying interest at PT. Sumber Cipta Multiniaga South Jakarta Branch. The method uses explanatory research and hypothesis testing with survey techniques, by distributing questionnaires using a saturated sampling technique of 100 respondents. The analytical tool used is descriptive and verification analysis or inverential with the test instruments and classical assumptions. The statistical analysis uses multiple regression tests, correlation coefficient values, coefficient of determination and hypothesis testing. The results of the study are promotion and a significant positive effect with a correlation of 0.576 and determination of 33.2%. Hypothesis testing obtained ρ value 0,000 <0.05. Price has a positive and significant effect on customer buying interest, with a correlation value of 0.645 and a determination of 41.6%. Hypothesis testing obtained ρ value 0,000 <0.05. Promotion and price simultaneously have a positive and significant effect on customer buying interest with a correlation value of 0.695 and a determination of 48.3% while the remaining 53.1% is influenced by other factors not examined. Hypothesis testing obtained ρ value 0,000 <0.05.This study aims to determine the effect of promotion and price on customer buying interest at PT. Sumber Cipta Multiniaga South Jakarta Branch. The method uses explanatory research and hypothesis testing with survey techniques, by distributing questionnaires using a saturated sampling technique of 100 respondents. The analytical tool used is descriptive and verification analysis or inverential with the test instruments and classical assumptions. The statistical analysis uses multiple regression tests, correlation coefficient values, coefficient of determination and hypothesis testing. The results of the study are promotion and a significant positive effect with a correlation of 0.576 and determination of 33.2%. Hypothesis testing obtained ρ value 0,000 <0.05. Price has a positive and significant effect on customer buying interest, with a correlation value of 0.645 and a determination of 41.6%. Hypothesis testing obtained ρ value 0,000 <0.05. Promotion and price simultaneously have a positive and significant effect on customer buying interest with a correlation value of 0.695 and a determination of 48.3% while the remaining 53.1% is influenced by other factors not examined. Hypothesis testing obtained ρ value 0,000 <0.05.